2016
DOI: 10.1186/s12967-016-0999-1
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes is associated with decreased PGC1α expression in epicardial adipose tissue of patients with coronary artery disease

Abstract: BackgroundAlthough recent studies indicate that epicardial adipose tissue expresses brown fat-like genes, such as PGC1α, UCP1 and PRDM16, the association of these genes with type 2 diabetes mellitus (DM2) in coronary artery disease (CAD) remains unknown.MethodsPGC1α, UCP1, and PRDM16 mRNAs expression levels were measured by real-time PCR in epicardial and thoracic subcutaneous adipose tissue from 44 CAD patients (22 with DM2 [CAD-DM2] and 22 without DM2 [CAD-NDM2]) and 23 non-CAD patients (NCAD).ResultsThe CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…However, there are some data showing that EAT contains BAT as well. Published studies or studies focused on the identification of EAT as brown-like tissue used gene expression such as PGC1α, UCP1 and PRDM16 mRNAs where adipose tissue was collected invasively usually during patient´s operation [18,19,20]. Moreover, some of these invasive studies showed that, depending on the presence of different type of adipose tissue, different cardiovascular and metabolic risks are present in patients.…”
Section: Discussion:-mentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are some data showing that EAT contains BAT as well. Published studies or studies focused on the identification of EAT as brown-like tissue used gene expression such as PGC1α, UCP1 and PRDM16 mRNAs where adipose tissue was collected invasively usually during patient´s operation [18,19,20]. Moreover, some of these invasive studies showed that, depending on the presence of different type of adipose tissue, different cardiovascular and metabolic risks are present in patients.…”
Section: Discussion:-mentioning
confidence: 99%
“…Moreover, some of these invasive studies showed that, depending on the presence of different type of adipose tissue, different cardiovascular and metabolic risks are present in patients. Moreno-Santos et al [18] showed that patients with type 2 diabetes and coronary artery disease exhibited a loss of brown-like fat features. This was also associated with higher prevalence of coronary lesions.…”
Section: Discussion:-mentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 This brite phenotype seems to decrease with age, diabetes mellitus and the severity of CAD. 12,13 There has been growing interest in the past decade in the non-invasive imaging of EAT volume as a predictor of future coronary events. 14 In the Heinz Nixdorf recall study, which included more than 4000 middle-aged participants, EAT volume measured by computed tomography (CT), was significantly associated with coronary events over the following 8 years.…”
mentioning
confidence: 99%